If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-32+3x=-4(8-8x)
We move all terms to the left:
-32+3x-(-4(8-8x))=0
We add all the numbers together, and all the variables
3x-(-4(-8x+8))-32=0
We calculate terms in parentheses: -(-4(-8x+8)), so:We get rid of parentheses
-4(-8x+8)
We multiply parentheses
32x-32
Back to the equation:
-(32x-32)
3x-32x+32-32=0
We add all the numbers together, and all the variables
-29x=0
x=0/-29
x=0
| 4y-4y=14 | | 30/7+2x=40 | | 18=x(2x) | | 168=-6v-8(v-7) | | 21=-19m-3 | | 168=-6v-8 | | 18=(x)(2x) | | 1/2(x+1)+4x=1/7x+2 | | -26-3x=1-8(-5x-2) | | X+x1/3+x1/3+x=64 | | 4a/3=6 | | -17=-5/9y-27 | | 39=-5x+24 | | 84-3b=24 | | 109=3(5n+4)-8 | | 14+x/5=8 | | 28-8x=6(-6-4x) | | -3x-5(10)=-71 | | 3x+4(10)=61 | | C(c+4)+5(c+4)=0 | | (-1+x)+(2x+1)=180 | | 3/2x+12=5/3 | | 2(-7)-5y=-64 | | 2(1)+8y=62 | | 4/3+2/5y=1/15 | | x+2(-10)=-28 | | 2(8n+10)=8n-52 | | -2(x-6)=12-2x | | 7-5x=10-(6×+7) | | 4(-1)+3y=26 | | 2(4−8x)+6=−1 | | 3x+1/2x+1=-6 |